Blast-induced damage and evaluation method of concrete gravity dam subjected to near-field underwater explosion. (15th April 2020) - Wang, Xiao-hua; Zhang, She-rong; Wang, Chao; Cui, Wei; Cao, Ke-lei; Fang, Xin
Highlights: Failure mechanism of dam exposed to underwater explosion has been investigated. Vibration characteristics are proved to assess the blast-induced damage of dam. Proposed equations are introduced to predict blast vibration of dam. An optimized criterion is proposed to evaluate the blast-induced damage of dam. Abstract: Bomb attacks from terrorists have become potential risks to important infrastructures, most of which were built without considering their vulnerability to such events. This paper focuses on the blast-induced damage to concrete gravity dams subjected to near-field underwater explosions. Different from direct damage mode analysis, a novel vibration-based damage evaluation method is proposed to illustrate the damage state of a dam after an explosion. To this end, a three-dimensional fluid-solid coupling numerical model in LS-DYNA is proposed for simulating the shock wave propagation and its interaction with dam structures, in which the explosive, air, and water are meshed by an arbitrary Lagrangian-Eulerian (ALE) formulation, while the dam and its foundation are meshed by the Lagrange formulation. Then, the structural responses and damage characteristics of the dam are investigated under various explosion scenarios considering changes in explosive charge, standoff distance and detonation depth. On this basis, the optimized vibration characteristics, including peak velocity summation (PVS) and mean frequency (MF), are adopted to evaluate the vulnerability of concrete gravity dams subjected to underwater explosions, which is better than the traditional damage evaluation method based solely on the peak particle velocity (PPV). The PVS-MF spectrum criterion proposed in this study is feasible to evaluate the damage state of concrete gravity dams after underwater explosions, and the results can be used in the blast-resistance design of similar hydraulic engineering.